PHARMACOKINETIC PROPERTIES OF A NEW KAPPA-OPIOID ANALGESIC RU-1205 COMPOUND AT A SINGLE PERORAL ADMINISTRATION - A. A. Spasov; L. A. Smirnova; O. Yu. Grechko; N. V. Eliseeva; Yu. V. Lifanova; A. I. Rashchenko; O. N. Zhukovskaya; A. S. Morkovnik; V. A. Anisimova (Фармация и фармакология (Пятигорск), 2021)
The aim of the study is the investigation of the pharmacokinetic properties of the RU-1205 compound, with previously identified kappa-agonistic and analgesic effects, at a single oral administration, as well as comparison of the relationship between its pharmacokinetic and analgesic properties.Materials and methods. Pharmacokinetic parameters of RU-1205 after the oral administration at the dose of 50 mg / kg were investigated using the method of High Performance Liquid Chromatography  with determination of the concentration of the compound according to the previously constructed calibration schedule. The indices of the area under the pharmacokinetic curve, clearance, half-life, residence time of the drug molecule in the body, a total (apparent) volume of distribution, as well as the indicator of absolute bioavailability, were calculated. The tissue distribution and excretion of RU-1205 were studied.Potential metabolites of RU-1205 were predicted using the PALLAS 3.00 program. The study of the analgesic activity was carried out on a model of central somatogenic pain with electricalstimulation, with the dynamics assessment of the voltage amplitude of the corresponding reaction of the "tail-flick" reflex.Results. The compound under study is rapidly adsorbed from the gastrointestinal tract, reaching a maximum concentration by the end of the first hour of the study, and is determined in plasma within 12 hours. Its half-life is 17.7 hours. The absolute oral bioavailability is 37.3%. It was found out that the compound is withdrawn within 3-4 days. The main route of excretion is extrarenal. Biotransformation of a substance probably proceeds mainly with the formation of oxidized forms of the initial molecule by reactions of the first phase of metabolic transformation. The analgesic effect is long-lasting: it starts after 15 minutes and lasts for 12 hours with flattening of the curve by the 8th hour.Conclusion. When administered orally, the test substance undergoes a long process of elimination, has the greatest tropism for the elimination organs and undergoes active biotransformation processes in the body of animals. As a result of it, active metabolic products with an analgesic activity are, possibly, formed.